Implementing Citizen’s Charter in Urban Local Government in Bangladesh: Do Accountability and Public Awareness Matter? - Sajib Kumar Roy; Mohammad Nur Ullah; Bikram Biswas; Md Mafizur Rahman (Universitas Sultan Ageng Tirtayasa, 2023)
Abstract: This research looks at the possibilities and challenges of adopting a Citizen’s Charter in Paurashava. In this regard, introducing the Citizen Charter in government offices is a step forward. One Paurashava was selected as the study field to observe the current situation of Citizen’s Charter implementation and to recognize the problems in Citizen’s Charter implementation. This study is primarily qualitative in nature. Both primary and secondary sources of data were used. Besides, official records and other relevant documents were used as secondary sources. According to preliminary observations, the extent of Citizen Charter implementation in Paurashava is extremely poor. All of the services of thePaurashava are not covered by the Citizen’s Charter, and most citizens are unaware of it. A number of other problems also hamper the success of the Paurashava. Therefore, these factors constrain the successful implementation of the Citizens’ Charter at the Paurashava.